American Science Fiction Television and Space Productions and (Re)configurations (1987-2021) - Hawkes, Joel.; Christie, Alexander; Nienhuis, Tom. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This collection explores how American science fiction television reflects, produces, and reconfigures the physical, imaginative, and cultural spaces we inhabit. It reads the proliferation of science fiction television and screen technologies as colliding heterotopias (impossible emplacements of space and time) that increasingly shape our world. With our growing awareness of population growth, the threat of ecocide, volatile geopolitics, and the rapid technological developments transforming media, we have become a "space conscious" age, with our lives increasingly mediated through the screen. Analyzing a plethora of science fiction television shows, the contributors explore science fiction's engagement with the contested nature of inhabiting space; consider science fiction and screens as mirrors reflecting and refracting our world, its politics and conflicts; examine the nature of intersecting media and the importance of screens as science-fictional devices; and assess the transformative effects of science fiction spaces on communities and bodies. Joel Hawkes lecturers in English at the University of Victoria, Canada. His research examines the practices and performances that create the physical and literary spaces we inhabit. His work is increasingly interested in how (television) screens shape our world. Recent papers appear in Surveillance, Architecture and Control: Discourses on Spatial Culture, Critical Approaches to 'Twin Peaks: The Return' and Screening American Nostalgia. Alexander Christie is Assistant Professor of Digital Prototyping at the Centre for Digital Humanities, Brock University, Canada. He has published internationally in a number of journals and collections, including Digital Humanities Quarterly, Social Knowledge Creation in the Humanities, and Reading Modernism with Machines. In addition to creating warped 3D maps of literary spaces (z-axis research), he is currently completing a book on modern manuscripts and humanities computing. Tom Nienhuis is an instructor in English at Camosun College in Victoria, Canada. His research examines religiosity and the supernatural in twentieth-century American literature. He is increasingly focused on science fiction storytelling, particularly cyber punk narratives.
1. Introduction, Joel Hawkes (Lecturer in English, University of Victoria); Alex Christie, PhD (Assistant Professor in Digital Prototyping, Brock University); Thomas Nienhuis (Lecturer in English, Camosun College) -- 2. Section One Introduction -- 3. Occupied Space: The Contested Habitation of Terok Nor/ Deep Space Nine, Ina Rae Hark (Distinguished Professor Emerita in Film and Media Studies, University of South Carolina) -- 4. Welwala at the Borders: Language, Space, and Power in The Expanse, Matt Barton (Professor in English, St. Cloud State University); Sharon Cogdill (Professor in English, St. Cloud State University); Michael B. Dando (Assistant Professor in English, St. Cloud State University); Ed Sadrai (Assistant Professor in English, St. Cloud State University) -- 5. "'You've Seen One Post-Apocalyptic City, You've Seen Them All': The Scales and Failures of the Right to the City and the Science Fiction Production of Space in Love, Death and Robots," Phevos Kallitsis (Senior Lecturer in Architecture, University of Portsmouth) -- 6. "Heaven is a Place on Earth"?: The Horizon of Queer Utopia in Black Mirror's "San Junipero," Orin Posner (PhD candidate in English, Tel-Aviv University) -- 7. SVOD: A Place for (Outer)Space? Andrew Lynch and Alexa Scarlata (PhD candidates in Culture and Communications, University of Melbourne) -- 8. Section Two Introduction -- 9. The Year Everything Changed: Babylon 2020, Alex Christie (Assistant Professor in Digital Prototyping, Brock University, editor of this collection) -- 10. The Wars of Ronald D. Moore: Terrorism, Insurgency, and News Media in Deep Space Nine and Battlestar Galactica, Benjamin Griffin (Professor and Major, United States Army, Fort Leavenworth) -- 11. "To ensure the safety of the Republic, we must deregulate the banks": A Social Democratic Reading of Star Wars: The Clone Wars, Edward Guimont (PhD candidate in History, University of Connecticut) -- 12. Enclosing and Opening the Spaces of Embodied Modernity in The Expanse, Edward Royston (Assistant Professor of English, Pfeiffer University) -- 13. Section Three Introduction -- 14. Prestige TV and the Corporate Long Con: Disembodied Spaces of Westworld, John Bruni (Adjunct Professor, School of Communication, Grand Valley State University) -- 15. Wading in the Upside-Down: Topsy-Turvy Media Spaces in Stranger Things, Nicolas Orlando (Humanities Instructor, Hillsborough Community College) -- 16. Memos from the Novel's Author: The Adaptation of Flash Forward for Television as a Series of Foucauldian Mirrors, Ellen Michelle (Editor, owner of Constellate Publishing) -- 17. Section Four Introduction -- 18. The Boys Keep Swinging, Sean Redmond (Professor of Screen and Design, Deakin University) -- 19. "I Am Also A We": Queer Slippage and Fan Activism in Netflix's Sense8, Alex Xanthoudakis (MA candidate in Publishing, Simon Fraser University) -- 20. Fringe and Dollhouse: Predicting the Apocalypse in the Spectral Bodies of Unconscious Viewers, Joel Hawkes (Lecturer in English, University of Victoria, editor of this collection) -- 21. Postscript, Mark Bould (University of West England).
Keywords: Television broadcasting; Motion pictures, American; Film genres; Space; Culture; Television Studies; American Film and TV; Genre Studies; Space and Place in Culture